Nebulized Fluticasone for Preventing Postextubation Stridor in Intubated Children: A Randomized, Double-Blind Placebo-Controlled Trial*. Issue 5 (May 2017) - Prasertsan, Pharsai; Nakju, Duangjai; Lertbunrian, Rojjanee; Chantra, Marut; Anantasit, Nattachai
Abstract : Objectives: To evaluate the efficacy of nebulized fluticasone propionate in the prevention of postextubation stridor in children. Design: Double-blind, placebo-controlled randomized clinical trial. Setting: PICU in a tertiary referral center. Patients: Children 1 month to 15 years old who underwent mechanical ventilation. Interventions: Patients were randomly assigned into two groups after stratification based on age group receiving nebulized fluticasone 1, 000 µg or normal saline solution, immediately after extubation. Vital signs and modified Westley score were evaluated for 6 hours after extubation. The primary outcome was the prevalence of postextubation stridor. Measurements and Main Results: One hundred forty-seven intubated children were enrolled into this study. Baseline characteristics between two groups were not different. There was no significant difference in the incidence of postextubation stridor (12/74 [16%] vs 13/73 [18%]; p = 0.797). However, when analyzing the subgroup of emergently intubated children, the fluticasone group had a longer delay median time for the initiation of noninvasive ventilation than the control group (380 [90–585] vs 60 [42–116] min; p = 0.044). The modified Westley scores at 30 and 60 minutes in the control group were significantly higher than the fluticasone group (4 vs 2, p = 0.04; 4.5 vs 0.5, p = 0.02, respectively). Conclusions: The single dose of 1, 000-µg nebulized fluticasone did not decrease the prevalence of postextubation stridor. However, it might be beneficial in emergently intubated children.